Caffeine improves basketball performance in experienced basketball players - Puente, C.; Abian-Vicen, J.; Salinero, J. J.; Lara, B.; Areces, F.; Del Coso, J. (Nutrients, 2017)
The aim of this study was to determine the effect of caffeine intake on overall basketball performance in experienced players. A double-blind, placebo-controlled, randomized experimental design was used for this investigation. In two different sessions separated by one week, 20 experienced basketball players ingested 3 mg of caffeine/kg of body mass or a placebo. After 60 min, participants performed 10 repetitions of the following sequence: Abalakov jump, Change-of-Direction and Acceleration Test (CODAT) and two free throws. Later, heart rate, body impacts and game statistics were recorded during a 20-min simulated basketball game. In comparison to the placebo, the ingestion of caffeine increased mean jump height (37.3 ± 6.8 vs. 38.2 ± 7.4 cm; p = 0.012), but did not change mean time in the CODAT test or accuracy in free throws. During the simulated game, caffeine increased the number of body impacts (396 ± 43 vs. 410 ± 41 impacts/min; p < 0.001) without modifying mean or peak heart rate. Caffeine also increased the performance index rating (7.2 ± 8.6 vs. 10.6 ± 7.1; p = 0.037) during the game. Nevertheless, players showed a higher prevalence of insomnia (19.0 vs. 54.4%; p = 0.041) after the game. Three mg of caffeine per kg of body mass could be an effective ergogenic substance to increase physical performance and overall success in experienced basketball players